A CASE OF CHEST GUNSHOT SHRAPNEL BLIND WOUND WITH MAMMARY GLAND DAMAGE - Khoroshun, E.M.; Makarov, V.V.; Nehoduiko, V.V.; Shypilov, S.A.; Panasenko, S.I.; Tertyshnyi, S.V.; Vastyanov, R.S. (World of Medicine and Biology, 2025)
The purpose of the study was to demonstrate the features of diagnosis and surgical treatment of gunshot shrapnel blind wound of the chest with damage to the mammary gland. Injured K., 27 years old, received a chest wound in a bulletproof vest while performing a combat mission after being dropped from a drone. An hour after the wound, she was delivered to the advanced surgical group in satisfactory condition, where a chest X-ray, antibiotic prophylaxis, tetanus toxoid, and dressing were performed. After 2 hours she was hospitalized with the following diagnosis: isolated gunshot shrapnel blind wound of the right breast. The surgical treatment was performed in the following scope: primary surgical treatment of the wound, removal of the foreign body (metal fragment). The foreign body was removed using a flexible device for removing ferromagnetic foreign bodies. Authors attracted attention that mammary glands gunshot wounds are a rare occurrence in general structure of gunshot wounds. The use of personal protective equipment does not always protect mammary glands from gunshot foreign bodies due to the poorly covered lateral surfaces. Authors concluded that modern surgical magnetic instrument use contributes to minimally invasive removal of gunshot foreign bodies from the mammary gland.
Keywords: gunshot wound; mammary gland; metal fragment; foreign body; magnetic detection